2024
DOI: 10.3390/nu16091277
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Trends in Planetary Health Diets among Nutrition Students in Türkiye: Bridging Classroom to Kitchen

Semra Navruz-Varlı,
Hande Mortaş,
Menşure Nur Çelik

Abstract: This study aimed to investigate the effects of sociodemographic parameters on healthy and sustainable nutrition in nutrition students. This cross-sectional study was conducted with 601 students. Researchers administered questionnaire forms to gather sociodemographic information such as age, gender, geographical region, residence area, accommodation, BMI, and income level. Participants’ 24 h dietary records were used to evaluate Healthy Eating Index-2020 (HEI-2020) and Planetary Health Diet Index (PHDI). The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The main reason for this situation is thought to be related to the higher level of nutritional knowledge of nutrition and dietetics students due to the vocational education they have received. A study conducted in students living in the Marmara region, which is the region where this study was conducted, and studying in a nutrition and dietetics department found that the mean HEI-2020 score of the students was 49.3 ± 10.4 [ 24 ]. In our study, while the HEI-2020 score for the Department of Nutrition and Dietetics students was 43.81 ± 14.11 before the course, it increased about 15 points two months after the course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason for this situation is thought to be related to the higher level of nutritional knowledge of nutrition and dietetics students due to the vocational education they have received. A study conducted in students living in the Marmara region, which is the region where this study was conducted, and studying in a nutrition and dietetics department found that the mean HEI-2020 score of the students was 49.3 ± 10.4 [ 24 ]. In our study, while the HEI-2020 score for the Department of Nutrition and Dietetics students was 43.81 ± 14.11 before the course, it increased about 15 points two months after the course.…”
Section: Discussionmentioning
confidence: 99%
“…The years of university education, which are considered young adulthood, constitute an important stage in which dietary habits that may influence nutrition status and overall health in later stages of life are established. Assessment of nutritional quality among university students is of great importance for promoting a healthier lifestyle in the years to come and protecting the environment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation